Laminate, packaging material, packaging bag and stand pouch
Patent Information
- Application Number
- JP2024089876
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-04
AI Technical Summary
Conventional packaging materials composed of different resin materials are difficult to recycle due to their non-homogeneous composition, lacking both strength and heat resistance, which hinders their recyclability.
A laminate structure is developed using polyethylene as both the base material and heat seal layer, with one surface of the base material subjected to electron beam irradiation, and optionally containing biomass-derived polyethylene, to enhance strength and heat resistance, ensuring a high polyethylene content of 90% or more in the laminate.
The laminate provides packaging materials with sufficient strength and recyclability, maintaining high polyethylene content for improved environmental sustainability while ensuring effective heat sealing and barrier properties.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, and a packaging material, a packaging bag, and a stand-up pouch formed from the laminate. [Background technology]
[0002] Conventionally, resin films made of resin materials have been used as materials for forming packaging materials. For example, resin films made of polyolefins have appropriate flexibility and transparency as well as excellent heat sealability, and therefore are widely used as packaging materials.
[0003] Generally, resin films made of polyolefins are inferior in strength and heat resistance and therefore cannot be used as a base material for constructing packaging materials, etc., and are used by laminating them with resin films made of polyester, polyamide, etc. For this reason, normal packaging materials are composed of a laminate in which the base material and the heat seal layer are made of different types of resin materials (for example, Patent Document 1).
[0004] In recent years, with the growing demand for the creation of a recycling-oriented society, there is a demand for high recyclability in packaging materials, etc. However, conventional packaging materials are composed of different resin materials as described above, and since it is difficult to separate each resin material, they are not currently recycled. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-202519 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present inventors have discovered that by subjecting a polyolefin film, specifically a polyethylene film, which has conventionally been used as a heat seal layer, to a stretching treatment and an electron beam irradiation treatment, the strength and heat resistance of the film can be significantly improved, and the film can be used as a base material for packaging materials, etc. Furthermore, the inventors discovered that by laminating the substrate with a heat seal layer made of polyethylene to form a laminate, it is possible to obtain a laminate that has high strength and heat resistance and can be used to produce recyclable packaging materials, etc.
[0007] The present invention has been made in view of the above findings, and the problem to be solved by the present invention is to provide a laminate that enables the production of a packaging material that has sufficient strength and excellent recyclability.
[0008] Another problem to be solved by the present invention is to provide a packaging material, a packaging bag, and a stand-up pouch which are formed from the laminate. [Means for solving the problem]
[0009] The laminate of the present invention comprises a substrate and a heat seal layer, The substrate is made of polyethylene, The substrate and the heat seal layer are made of the same material, At least one surface of the substrate is irradiated with an electron beam; The same material is polyethylene, At least one of the substrate and the heat seal layer contains biomass-derived polyethylene as the polyethylene; The substrate is provided so that the surface of the substrate that is irradiated with the electron beam is the outermost surface.
[0010] In one embodiment, the thickness of the substrate is 10 μm or more and 50 μm or less.
[0011] In one embodiment, the stretching ratio of the substrate in the longitudinal direction and / or transverse direction is 2 times or more and 10 times or less.
[0012] In one embodiment, the laminate of the present invention is used in packaging applications.
[0013] The packaging material of the present invention is characterized in that it is constituted by the above-mentioned laminate.
[0014] The packaging bag of the present invention is composed of the above-mentioned laminate, The thickness of the heat seal layer is 20 μm or more and 60 μm or less.
[0015] The stand-up pouch of the present invention is constituted by the above-mentioned laminate, The heat seal layer has a thickness of 50 μm or more and 200 μm or less. Effect of the Invention
[0016] According to the present invention, it is possible to provide a laminate that enables the production of a packaging material that has sufficient strength and is also highly recyclable. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a cross-sectional schematic diagram illustrating one embodiment of a substrate. [Diagram 2] FIG. 2 is a cross-sectional schematic diagram illustrating one embodiment of a substrate. [Diagram 3] 1 is a schematic cross-sectional view showing one embodiment of a laminate of the present invention. [Figure 4] FIG. 1 is a perspective view showing one embodiment of a packaging material produced using a laminate of the present invention. [Diagram 5] FIG. 1 is a perspective view showing one embodiment of a packaging material produced using a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] (Laminate) As shown in FIG. 1, a laminate 10 of the present invention includes a substrate 11 and a heat seal layer 12.
[0019] In one embodiment, the laminate 11 of the present invention includes an intermediate layer 13 between the substrate 10 and the heat seal layer 12, as shown in FIG.
[0020] In one embodiment, the laminate of the present invention may include an adhesive layer 14 between any of the layers, as shown in FIGS.
[0021] The content of polyethylene in the entire laminate of the present invention is preferably 90% by mass or more, and more preferably 90% by mass or more. By making the polyethylene content in the entire laminate of the present invention 90% by mass or more, the recyclability of the laminate of the present invention can be improved.
[0022] Each layer constituting the laminate of the present invention will now be described.
[0023] (base material) The substrate is a film made of polyethylene, which is characterized by having been stretched and having at least one surface thereof subjected to electron beam irradiation treatment. In this way, by stretching a film made of polyethylene and irradiating at least one surface of the film with an electron beam to increase the crosslink density of the polyethylene, the heat resistance and strength of the film can be significantly improved, and the film can satisfy the physical properties required for an outer layer of a packaging material, etc. Furthermore, by forming the substrate and the heat seal layer described below from polyethylene, the recyclability of the laminate can be improved. Furthermore, in the present invention, at least one of the polyethylene constituting the substrate and the heat seal layer contains biomass-derived polyethylene as the polyethylene, and this makes it possible to make the packaging material produced from the laminate of the present invention more environmentally friendly.
[0024] As the polyethylene, high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene and very low density polyethylene can be used. Among these, high density polyethylene and medium density polyethylene are preferred from the viewpoint of the strength and heat resistance of the substrate, and medium density polyethylene is more preferred from the viewpoint of the stretchability.
[0025] In the present invention, the high density polyethylene has a density of 0.945 g / cm 3 The polyethylene having a density of 0.925 g / cm3 or more can be used. 3 More than 0.945g / cm 3 Polyethylene having a density of less than 0.900 g / cm3 can be used. 3 More than 0.925g / cm 3 For linear low density polyethylene, a polyethylene having a density of 0.900 g / cm3 or less can be used. 3 More than 0.925g / cm 3 For ultra-low density polyethylene, a polyethylene having a density of 0.900 g / cm3 can be used. 3 Less than 100 mm of polyethylene can be used.
[0026] The polyethylenes having different densities and branches as described above can be obtained by appropriately selecting a polymerization method. For example, it is preferable to use a multi-site catalyst such as a Ziegler-Natta catalyst or a single-site catalyst such as a metallocene catalyst as a polymerization catalyst and carry out the polymerization in one stage or in two or more stages by any of gas phase polymerization, slurry polymerization, solution polymerization, and high pressure ion polymerization.
[0027] The single-site catalyst is a catalyst capable of forming a uniform active species, and is usually prepared by contacting a metallocene transition metal compound or a nonmetallocene transition metal compound with an activating cocatalyst. Compared with a multi-site catalyst, a single-site catalyst is preferred because it has a uniform active site structure and can polymerize a polymer with a high molecular weight and a highly uniform structure. As the single-site catalyst, it is particularly preferred to use a metallocene catalyst. The metallocene catalyst is a catalyst containing each catalyst component of a transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, a cocatalyst, and if necessary, an organometallic compound and a carrier.
[0028] In the above-mentioned transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the cyclopentadienyl skeleton is a cyclopentadienyl group, a substituted cyclopentadienyl group, etc. The substituted cyclopentadienyl group has at least one substituent selected from a hydrocarbon group having 1 to 30 carbon atoms, a silyl group, a silyl-substituted alkyl group, a silyl-substituted aryl group, a cyano group, a cyanoalkyl group, a cyanoaryl group, a halogen group, a haloalkyl group, a halosilyl group, etc. The substituted cyclopentadienyl group may have two or more substituents, and the substituents may be bonded to each other to form a ring, such as an indenyl ring, a fluorenyl ring, an azulenyl ring, or a hydrogenated product thereof. The rings formed by bonding the substituents to each other may further have substituents.
[0029] In the transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton, the transition metal may be zirconium, titanium, hafnium, etc., and zirconium and hafnium are particularly preferred. The transition metal compound usually has two ligands having a cyclopentadienyl skeleton, and it is preferred that the ligands having each cyclopentadienyl skeleton are bonded to each other by a bridging group. Examples of the bridging group include an alkylene group having 1 to 4 carbon atoms, a silylene group, a substituted silylene group such as a dialkylsilylene group or a diarylsilylene group, and a substituted germylene group such as a dialkylgermylene group or a diarylgermylene group. The substituted silylene group is preferred. The above-mentioned transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton may be used as a catalyst component, either alone or in a mixture of two or more kinds.
[0030] The co-catalyst refers to a catalyst that can effectively use the above-mentioned transition metal compound of Group IV of the periodic table as a polymerization catalyst or balance the ionic charge in a catalytically activated state. Examples of the co-catalyst include benzene-soluble aluminoxanes of organoaluminum oxy compounds and benzene-insoluble organoaluminum oxy compounds, ion-exchangeable layered silicates, boron compounds, ionic compounds consisting of cations containing or not containing active hydrogen groups and non-coordinating anions, lanthanoid salts such as lanthanum oxide, tin oxide, and phenoxy compounds containing fluoro groups.
[0031] The transition metal compound of Group IV of the periodic table containing a ligand having a cyclopentadienyl skeleton may be used by being supported on an inorganic or organic carrier. The carrier is preferably an inorganic or organic porous oxide, and specifically includes ion-exchangeable layered silicates such as montmorillonite, SiO2, Al2O3, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, and mixtures thereof. Furthermore, examples of organometallic compounds that are used as needed include organoaluminum compounds, organomagnesium compounds, and organozinc compounds. Of these, organoaluminum compounds are preferably used.
[0032] In addition, copolymers of ethylene and other monomers can also be used within the scope of the present invention. Examples of ethylene copolymers include copolymers of ethylene and α-olefins having 3 to 20 carbon atoms, and examples of α-olefins having 3 to 20 carbon atoms include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, 4-methyl-1-pentene, and 6-methyl-1-heptene. In addition, copolymers with vinyl acetate or acrylic esters can be used within the scope of the present invention.
[0033] In the present invention, the substrate preferably contains polyethylene derived from biomass. Biomass-derived polyethylene is polyethylene obtained by using biomass-derived ethylene as a raw material instead of ethylene obtained from fossil fuels.
[0034] In one embodiment, plant-derived ethylene can be obtained by fermenting sugar liquid or starch obtained from plants such as sugar cane, corn, and sweet potato with a microorganism such as yeast to produce bioethanol, and then heating the bioethanol in the presence of a catalyst. Furthermore, as the biomass-derived polyethylene, commercially available products (for example, Green PE available from Braskem) may be used.
[0035] It is also possible to use polyethylene recycled by mechanical recycling. Mechanical recycling generally refers to a method in which collected polyethylene films are crushed and washed with an alkali to remove dirt and foreign matter from the film surface, and then dried at high temperature and reduced pressure for a certain period of time to diffuse and decontaminate the contaminants remaining inside the film, removing dirt from the polyethylene film and returning it to polyethylene.
[0036] The content of biomass-derived polyethylene in the substrate is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more.
[0037] The substrate may contain additives within the range that does not impair the characteristics of the present invention. Examples of such additives include crosslinking agents, antioxidants, antiblocking agents, slip agents, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, pigments, and modifying resins.
[0038] In one embodiment, the substrate has a multi-layer structure. In one embodiment, the substrate comprises a layer made of high density polyethylene (hereinafter referred to as high density polyethylene layer), a layer made of medium density polyethylene (hereinafter referred to as medium density polyethylene layer), and a layer made of high density polyethylene (hereinafter referred to as high density polyethylene layer). By adopting such a configuration, it is possible to further improve the strength and heat resistance of the substrate while maintaining its stretchability. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 10 or more, the strength and heat resistance of the substrate can be further improved. Also, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 1 or less, the stretchability of the substrate can be further improved.
[0039] In one embodiment, the substrate comprises a high density polyethylene layer, a medium density polyethylene layer, a low density polyethylene layer, a linear low density polyethylene layer or an ultra low density polyethylene layer (collectively referred to as a low density polyethylene layer in this paragraph for the sake of simplicity), a medium density polyethylene layer and a high density polyethylene layer. By adopting such a configuration, it is possible to improve the stretchability of the substrate, to improve the strength and heat resistance of the substrate, to prevent the substrate from curling, and to improve the production efficiency of the substrate. In this case, the thickness of the high density polyethylene layer is preferably thinner than the thickness of the medium density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the medium density polyethylene layer is preferably 1 / 10 or more and 1 / 1 or less, and more preferably 1 / 5 or more and 1 / 2 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 10 or more, the strength and heat resistance of the substrate can be improved, and by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the medium-density polyethylene layer to 1 / 1 or less, the stretchability of the substrate can be improved. In addition, the thickness of the high density polyethylene layer is preferably the same as or greater than the thickness of the low density polyethylene layer. The ratio of the thickness of the high density polyethylene layer to the thickness of the low density polyethylene layer is preferably 1 / 0.25 or more and 1 / 2 or less, and more preferably 1 / 0.5 or more and 1 / 1 or less. By setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer to 1 / 0.25 or more, the heat resistance of the substrate can be improved. Also, by setting the ratio of the thickness of the high-density polyethylene layer to the thickness of the low-density polyethylene layer to 1 / 1 or less, the adhesion between the medium-density polyethylene layers can be improved. In one embodiment, a substrate having such a configuration can be produced by, for example, an inflation method. Specifically, the film can be produced by co-extruding, from the outside, a high-density polyethylene layer, a medium-density polyethylene layer, and a low-density polyethylene layer, a linear low-density polyethylene layer, or an ultra-low-density polyethylene layer into a tubular shape, and then pressing the opposing low-density polyethylene layers, linear low-density polyethylene layers, or ultra-low-density polyethylene layers together using a rubber roll or the like. By using such a method, the number of defective products during manufacturing can be significantly reduced, and ultimately, production efficiency can be improved. In addition, the stretching can also be carried out in the inflation film forming machine, which can further improve the production efficiency.
[0040] The substrate may be a uniaxially or biaxially oriented film. The stretching ratio in the machine direction (MD) of the substrate is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. By making the stretching ratio in the longitudinal direction (MD) of the substrate 2 times or more, the strength and heat resistance of the substrate of the present invention can be improved. Furthermore, the printability of the substrate can be improved. Furthermore, the transparency of the substrate can be improved. On the other hand, the upper limit of the stretching ratio in the longitudinal direction (MD) of the substrate is not particularly limited, but it is preferably 10 times or less from the viewpoint of the breaking limit of the substrate. The stretch ratio in the transverse direction (TD) of the substrate is preferably 2 times or more and 10 times or less, and more preferably 3 times or more and 7 times or less. By setting the stretch ratio in the transverse direction (TD) of the substrate to 2 times or more, the strength and heat resistance of the substrate of the present invention can be improved. Furthermore, the printability of the substrate can be improved. Furthermore, the transparency of the substrate can be improved. On the other hand, the upper limit of the stretch ratio in the transverse direction (TD) of the substrate is not particularly limited, but is preferably 10 times or less from the viewpoint of the breaking limit of the substrate.
[0041] The substrate 10 may be one in which the crosslink density of polyethylene on one side has been improved by electron beam irradiation, as shown in Figures 1 and 2, or may be one in which the crosslink density of polyethylene has been improved throughout the substrate, as shown in Figure 3. When the substrate has a multi-layer structure, it is sufficient that the crosslink density of at least the polyethylene in the outermost layer is improved by electron beam irradiation. From the viewpoint of strength and heat resistance, it is preferable that the crosslink density of the polyethylene as a whole is improved by electron beam irradiation.
[0042] As an apparatus that can be used for irradiating the substrate with an electron beam, a conventionally known apparatus can be used. For example, a curtain-type electron irradiation apparatus (LB1023, manufactured by I-Electron Beam Co., Ltd.), a line-irradiation type low-energy electron beam irradiation apparatus (EB-ENGINE, manufactured by Hamamatsu Photonics K.K.), and a drum roll-type electron beam irradiation apparatus (EZ-CURE, manufactured by I-Electron Beam Co., Ltd.) can be suitably used.
[0043] The dose of the electron beam irradiated onto the substrate is preferably in the range of 10 kGy to 2000 kGy, more preferably in the range of 20 kGy to 1000 kGy. The accelerating voltage of the electron beam is preferably in the range of 30 kV or more and 300 kV or less, more preferably in the range of 50 kV or more and 300 kV or less, and even more preferably in the range of 50 kV or more and 250 kV or less. Furthermore, the irradiation energy of the electron beam is preferably in the range of 20 keV or more and 750 keV or less, more preferably in the range of 25 keV or more and 500 keV or less, even more preferably in the range of 30 keV or more and 400 keV or less, and particularly preferably in the range of 20 keV or more and 200 keV or less.
[0044] The oxygen concentration in the electron beam irradiation device is preferably 500 ppm or less, more preferably 100 ppm or less. By performing electron beam irradiation under such conditions, it is possible to suppress the generation of ozone and also to suppress the radicals generated by electron beam irradiation from being deactivated by oxygen in the atmosphere. Such conditions can be achieved, for example, by making the inside of the device an inert gas (nitrogen, argon, etc.) atmosphere.
[0045] In one embodiment, the irradiation with the electron beam can be performed simultaneously with cooling using a cooling drum or the like.
[0046] The substrate may be subjected to a surface treatment, which can improve adhesion between adjacent layers when the substrate is formed into a laminate as described below. The method of surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals. Furthermore, an anchor coat layer may be formed on the surface of the substrate using a conventionally known anchor coat agent.
[0047] The substrate may have an image formed on its surface. The image to be formed is not particularly limited, and may represent letters, patterns, symbols, combinations of these, and the like. The image formation on the substrate is preferably carried out using ink derived from biomass, and this allows the substrate to be used to produce packaging materials and the like that have a lower environmental impact. The method for forming the image is not particularly limited, and examples of the method include conventionally known printing methods such as gravure printing, offset printing, flexographic printing, etc. Among these, flexographic printing is preferred from the viewpoint of environmental load.
[0048] In one embodiment, the substrate may have a vapor-deposited film on the surface thereof on which the heat seal layer is laminated, thereby improving the gas barrier properties, specifically the oxygen barrier properties and water vapor barrier properties, of the substrate.
[0049] Examples of the vapor-deposited film include vapor-deposited films composed of metals such as aluminum, and inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide.
[0050] The thickness of the evaporated film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less. By making the thickness of the vapor-deposited film 1 nm or more, the oxygen barrier property and water vapor barrier property of the substrate can be further improved. Also, by making the thickness of the vapor-deposited film 150 nm or less, the occurrence of cracks in the vapor-deposited film can be prevented. Also, when the substrate is applied to the laminate described below, the recyclability can be maintained.
[0051] In one embodiment, the substrate comprises a barrier coat layer, which can improve the oxygen barrier property and water vapor barrier property of the substrate. When the substrate has a vapor-deposited film, the barrier coat layer may be provided on or under the vapor-deposited film.
[0052] In one embodiment, the barrier coat layer contains a gas barrier resin such as an ethylene-vinyl alcohol copolymer (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamide such as nylon 6, nylon 6,6, and polymetaxylylene adipamide (MXD6), polyester, polyurethane, and (meth)acrylic resin. Among these, polyvinyl alcohol is preferred from the viewpoint of oxygen barrier property and water vapor barrier property. Furthermore, when the vapor-deposited film is made of an inorganic oxide, the occurrence of cracks in the vapor-deposited film can be effectively prevented by including polyvinyl alcohol in the barrier coat layer.
[0053] The content of the gas barrier resin in the barrier coat layer is preferably 50% by mass or more and 95% by mass or less, and more preferably 75% by mass or more and 90% by mass or less. By making the content of the gas barrier resin in the barrier coat layer 50% by mass or more, the oxygen barrier property and water vapor barrier property of the substrate can be further improved.
[0054] The barrier coat layer may contain the above-mentioned additives to the extent that the characteristics of the present invention are not impaired.
[0055] The thickness of the barrier coat layer is preferably 0.01 μm or more and 10 μm or less, and more preferably 0.1 μm or more and 5 μm or less. By making the thickness of the barrier coat layer 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the substrate can be further improved, and by making the thickness of the barrier coat layer 10 μm or less, the recyclability can be maintained when the substrate is applied to the laminate described below.
[0056] The barrier coat layer can be formed by dissolving or dispersing the above-mentioned material in water or a suitable solvent, applying the solution, and drying the solution. Alternatively, the barrier coat layer can be formed by applying a commercially available barrier coat agent and drying the solution.
[0057] In another embodiment, the barrier coat layer is a gas barrier coating film containing at least one resin composition such as a hydrolysate of a metal alkoxide or a hydrolyzed condensate of a metal alkoxide obtained by polycondensing a mixture of a metal alkoxide and a water-soluble polymer by a sol-gel method in the presence of a sol-gel catalyst, water, an organic solvent, etc. When the substrate has a vapor-deposited film made of an inorganic oxide, by providing the barrier coat layer of this type adjacent to the vapor-deposited film, it is possible to effectively prevent the occurrence of cracks in the vapor-deposited film.
[0058] In one embodiment, the metal alkoxide is represented by the following general formula: R 1 n M(OR 2 ) m (In the formula, R 1 , R 2 each represents an organic group having 1 to 8 carbon atoms, M represents a metal atom, n represents an integer of 0 or more, m represents an integer of 1 or more, and n+m represents the atomic valence of M.
[0059] As the metal atom M, for example, silicon, zirconium, titanium, aluminum, etc. can be used. Also, R 1 and R 2 Examples of the organic group represented by the formula (I) include alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, and an i-butyl group.
[0060] Examples of metal alkoxides that satisfy the above general formula include tetramethoxysilane (Si(OCH3)4), tetraethoxysilane (mass %) Si(OC2H5)4), tetrapropoxysilane (Si(OC3H7)4), and tetrabutoxysilane (Si(OC4H9)4).
[0061] It is also preferable to use a silane coupling agent together with the metal alkoxide. As the silane coupling agent, known organic reactive group-containing organoalkoxysilanes can be used, and in particular, organoalkoxysilanes having epoxy groups are preferred. As organoalkoxysilanes having epoxy groups, for example, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane can be mentioned.
[0062] Two or more of the above silane coupling agents may be used, and the silane coupling agent is preferably used in an amount within the range of about 1 to 20 parts by mass per 100 parts by mass of the total amount of the alkoxide.
[0063] As the water-soluble polymer, polyvinyl alcohol and an ethylene-vinyl alcohol copolymer are preferred, and from the viewpoints of oxygen barrier properties, water vapor barrier properties, water resistance and weather resistance, it is preferred to use these in combination.
[0064] The content of the water-soluble polymer in the gas barrier coating film is preferably 5 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the metal alkoxide. By making the content of the water-soluble polymer in the gas barrier coating film 5 parts by mass or more per 100 parts by mass of the metal alkoxide, the oxygen barrier property and water vapor barrier property of the substrate can be further improved. Also, by making the content of the water-soluble polymer in the gas barrier coating film 500 parts by mass or less per 100 parts by mass of the metal alkoxide, the film formability of the gas barrier coating film can be improved.
[0065] The thickness of the gas barrier coating film is preferably from 0.01 μm to 100 μm, and more preferably from 0.1 μm to 50 μm, which can improve the oxygen barrier property and water vapor barrier property while maintaining recyclability. By making the thickness of the gas barrier coating film 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the substrate can be improved. In addition, when the gas barrier coating film is provided adjacent to a vapor deposition film made of an inorganic oxide, the occurrence of cracks in the vapor deposition film can be prevented.
[0066] The gas barrier coating film can be formed by applying a composition containing the above-mentioned materials by a conventionally known means such as roll coating using a gravure roll coater or the like, spray coating, spin coating, dipping, brushing, bar coding, or an applicator, and then polycondensing the composition by a sol-gel method. As the sol-gel catalyst, an acid or an amine compound is preferable. As the amine compound, a tertiary amine that is substantially insoluble in water and soluble in an organic solvent is preferable, and examples thereof include N,N-dimethylbenzylamine, tripropylamine, tributylamine, and tripentylamine. Among these, N,N-dimethylbenzylamine is preferable. The sol-gel catalyst is preferably used in the range of 0.01 to 1.0 part by mass, and more preferably 0.03 to 0.3 part by mass, per 100 parts by mass of the metal alkoxide. By using a sol-gel catalyst in an amount of 0.01 part by mass or more per 100 parts by mass of the metal alkoxide, the catalytic effect can be improved, and by using a sol-gel catalyst in an amount of 1.0 part by mass or less per 100 parts by mass of the metal alkoxide, the thickness of the gas barrier coating film formed can be made uniform.
[0067] The composition may further contain an acid, which is used as a catalyst in the sol-gel process, mainly for the hydrolysis of alkoxides, silane coupling agents, and the like. The acid may be a mineral acid such as sulfuric acid, hydrochloric acid, or nitric acid, or an organic acid such as acetic acid, tartaric acid, etc. The amount of the acid used is preferably 0.001 mol or more and 0.05 mol or less based on the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent. The amount of acid used is 0.001 moles or more relative to the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent, thereby improving the catalytic effect. Also, the amount of acid used is 0.05 moles or less relative to the total molar amount of the alkoxide and the alkoxide portion (e.g., silicate portion) of the silane coupling agent, thereby making the thickness of the gas barrier coating film formed uniform.
[0068] The composition preferably contains water in an amount of 0.1 to 100 moles, more preferably 0.8 to 2 moles, per mole of the total molar amount of the alkoxides. By controlling the water content to 0.1 moles or more per mole of the total molar amount of the alkoxides, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be improved. Also, by controlling the water content to 100 moles or more per mole of the total molar amount of the alkoxides, the hydrolysis reaction can be carried out quickly.
[0069] The composition may also contain an organic solvent, such as methyl alcohol, ethyl alcohol, n-propyl alcohol, isopropyl alcohol, or n-butanol.
[0070] Hereinafter, one embodiment of the method for forming a gas barrier coating film will be described. First, a composition is prepared by mixing a metal alkoxide, a water-soluble polymer, a sol-gel catalyst, water, an organic solvent, and optionally a silane coupling agent, etc. In the composition, a polycondensation reaction gradually proceeds. Next, the composition is applied onto the polyolefin resin layer by the above-mentioned conventionally known method and dried. This drying process further advances the polycondensation reaction between the alkoxide and the water-soluble polymer (and the silane coupling agent, if the composition contains a silane coupling agent) to form a composite polymer layer. Finally, the composition is heated at a temperature of 20 to 250° C., preferably 50 to 220° C., for 1 second to 10 minutes to form a gas barrier coating film.
[0071] The barrier coat layer may have an image formed on its surface. The method for forming the image is as described above.
[0072] The thickness of the substrate is preferably 10 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. By making the thickness of the substrate 10 μm or more, the strength required for the substrate of packaging materials etc. can be fully satisfied. Also, by making the thickness of the substrate 50 μm or less, the processability of the substrate can be improved.
[0073] The substrate can be produced by forming a resin composition containing at least polyethylene into a film using a T-die method, an inflation method or the like to form a resin film, followed by stretching and irradiating with an electron beam. By forming the film by the inflation method, the resin film can be stretched at the same time. Either the stretching of the resin film or the electron beam irradiation may be carried out first, but from the standpoint of suitability for stretching, it is preferable to carry out the stretching step first.
[0074] When the substrate is produced by the T-die method, the MFR of the resin composition is preferably 3 g / 10 min or more and 20 g / 10 min or less. By setting the MFR of the resin composition to 3 g / 10 min or more, the processability of the substrate can be improved, and by setting the MFR of the resin composition to 20 g / 10 min or less, the substrate can be prevented from breaking.
[0075] When the substrate is produced by an inflation method, the MFR of the resin composition is preferably 0.5 g / 10 min or more and 5 g / 10 min or less. By setting the MFR of the resin composition to 0.5 g / 10 min or more, the processability of the substrate can be improved, and by setting the MFR of the resin composition to 5 g / 10 min or less, the film formability can be improved.
[0076] The deposition film on the substrate can be formed by a conventional method, for example, physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.
[0077] Also, for example, a composite film consisting of two or more layers of vapor-deposited films of different inorganic oxides can be formed and used by combining both physical vapor deposition and chemical vapor deposition. The degree of vacuum in the vapor deposition chamber is 10 -2 ~10 -8 After oxygen is introduced, the pressure is preferably about 10 -1 ~10 -6The pressure is preferably about mbar. The amount of oxygen introduced varies depending on the size of the deposition machine. For the oxygen to be introduced, an inert gas such as argon gas, helium gas, or nitrogen gas may be used as a carrier gas to the extent that no problems occur. The film transport speed can be about 10 to 800 m / min.
[0078] The surface of the deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers when applied to the laminate described below.
[0079] (Heat seal layer) The heat seal layer is characterized by being composed of polyethylene. Since the laminate of the present invention is composed of a base material and a heat seal layer composed of polyethylene, it is possible to improve the recyclability of packaging materials and the like produced using the laminate. However, the heat seal layer is formed from an unstretched polyolefin resin film or by melt extrusion of polyolefin.
[0080] From the viewpoint of heat sealability, it is preferable to use low density polyethylene, linear low density polyethylene, and very low density polyethylene as the polyethylene. From the viewpoint of environmental impact, the heat seal layer preferably contains the above-mentioned biomass-derived polyethylene. Mechanically recycled polyethylene can also be used.
[0081] The content of biomass-derived polyethylene in the heat seal layer is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more.
[0082] In one embodiment, the heat seal layer has a multi-layer structure and includes, as an intermediate layer, a layer containing at least one of medium density polyethylene and high density polyethylene. Specifically, the laminate may be configured as follows: a layer containing at least one of low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene; a layer containing at least one of medium-density polyethylene and high-density polyethylene; and a layer containing at least one of low-density polyethylene, linear low-density polyethylene, and very low-density polyethylene. The intermediate layer may also be a layer made of polyethylene derived from biomass. By adopting the above-mentioned configuration, the bag-making suitability and strength of the laminate of the present invention can be further improved while maintaining the heat sealability.
[0083] It is preferable that the thickness of the heat seal layer is appropriately changed depending on the weight of the contents to be filled in the packaging material produced from the laminate of the present invention. For example, when preparing a packaging bag as shown in FIG. 5 for filling a content of 1 g or more and 200 g or less, the thickness of the heat seal layer is preferably 20 μm or more and 60 μm or less. By making the thickness of the heat seal layer 20 μm or more, it is possible to prevent the leakage of the filled contents due to damage to the heat seal layer, and by making the thickness of the heat seal layer 60 μm or less, it is possible to improve the processability of the laminate of the present invention.
[0084] Furthermore, for example, when preparing a stand pouch as shown in FIG. 6 for filling with contents of 50 g or more and 2000 g or less, the thickness of the heat seal layer is preferably 50 μm or more and 200 μm or less. By making the thickness of the heat seal layer 50 μm or more, it is possible to prevent the filled contents from leaking due to damage to the heat seal layer, and by making the thickness of the heat seal layer 200 μm or less, it is possible to improve the processability of the laminate of the present invention. The shaded areas in Figures 4 and 5 are heat-sealed areas.
[0085] The heat seal layer may have a vapor-deposited film on the surface of the substrate side thereof, which can improve the oxygen barrier property and water vapor barrier property.
[0086] Examples of the vapor-deposited film include vapor-deposited films composed of metals such as aluminum, and inorganic oxides such as aluminum oxide, silicon oxide, magnesium oxide, calcium oxide, zirconium oxide, titanium oxide, boron oxide, hafnium oxide, and barium oxide.
[0087] The thickness of the evaporated film is preferably 1 nm or more and 150 nm or less, more preferably 5 nm or more and 60 nm or less, and even more preferably 10 nm or more and 40 nm or less.
[0088] The method for forming the vapor-deposited film is as described above.
[0089] The surface of the deposited film is preferably subjected to the above-mentioned surface treatment, which can improve adhesion to adjacent layers.
[0090] (Middle class) In one embodiment, the intermediate layer comprises an oriented polyethylene film, which can provide additional strength to the laminate of the present invention. The oriented polyethylene film is made of polyethylene, and high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene and very low density polyethylene can be used. From the viewpoint of environmental load, the intermediate layer preferably contains the above-mentioned biomass-derived polyethylene. Mechanically recycled polyethylene can also be used.
[0091] The content of biomass-derived polyethylene in the middle is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more.
[0092] The stretched polyethylene film may have the above-mentioned multi-layer structure.
[0093] The stretched polyethylene film may be a uniaxially stretched film or a biaxially stretched film, and the preferred stretch ratio is as described above.
[0094] The thickness of the stretched polyethylene film is preferably 10 μm or more and 50 μm or less, and more preferably 12 μm or more and 30 μm or less. By making the thickness of the stretched polyethylene film 10 μm or more, the strength and heat resistance of the laminate of the present invention can be improved, and by making the thickness of the stretched polyethylene film 50 μm or less, the processability of the laminate can be improved.
[0095] In one embodiment, the intermediate layer includes a gas barrier layer made of a gas barrier resin. By including such an intermediate layer in the laminate of the present invention, the oxygen barrier property and water vapor barrier property can be improved. Examples of gas barrier resins include ethylene-vinyl alcohol copolymers (EVOH), polyvinyl alcohol, polyacrylonitrile, polyamides such as nylon 6, nylon 6,6 and polymetaxylylene adipamide (MXD6), polyesters, polyurethanes, and (meth)acrylic resins.
[0096] The thickness of the gas barrier layer is preferably from 0.01 μm to 10 μm, and more preferably from 0.1 μm to 5 μm. By making the thickness of the gas barrier layer 0.01 μm or more, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be further improved, and by making the thickness of the gas barrier layer 10 μm or less, the recyclability of the laminate of the present invention can be maintained.
[0097] In one embodiment, the intermediate layer comprises a vapor-deposited film. The form, preferred thickness, and formation method of the vapor-deposited film that can be used are as described above.
[0098] In one embodiment, the intermediate layer comprises a barrier coat layer, the configuration, preferred thickness, forming method, etc. of which are as described above.
[0099] (adhesive layer) The laminate of the present invention may have an adhesive layer between any of the layers, thereby improving the adhesion between the layers.
[0100] The adhesive layer may be formed from a conventionally known adhesive, which may be a one-component curing type, a two-component curing type, or a non-curing type. The adhesive may be either a solvent-free adhesive or a solvent-based adhesive, but from the standpoint of environmental impact, a solvent-free adhesive is preferably used. Examples of solvent-free adhesives include polyether adhesives, polyester adhesives, silicone adhesives, epoxy adhesives, and urethane adhesives, and among these, two-component curing urethane adhesives can be preferably used. Examples of the solvent-based adhesive include rubber-based adhesives, vinyl-based adhesives, silicone-based adhesives, epoxy-based adhesives, phenol-based adhesives, and olefin-based adhesives.
[0101] In addition, when the adhesive layer is provided so as to be adjacent to the aluminum vapor deposition film, it is preferable that the adhesive layer is composed of a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound. By configuring the adhesive layer in this way, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be further improved. Furthermore, when the laminate with the vapor-deposited film is molded into a packaging material, a bending load is applied to the laminate by a molding machine or the like, which may cause cracks in the aluminum vapor-deposited film. By configuring the adhesive layer as described above, it is possible to suppress a decrease in the oxygen barrier property and water vapor barrier property (flexural load resistance) even if cracks occur in the aluminum vapor-deposited film.
[0102] The polyester polyol has two or more hydroxyl groups as functional groups in one molecule. The isocyanate compound has two or more isocyanate groups as functional groups in one molecule. The polyester polyol has, for example, a polyester structure or a polyester polyurethane structure as a main skeleton.
[0103] As a specific example of a resin composition (adhesive) containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound, the PASLIM series sold by DIC Corporation can be used.
[0104] The resin composition may further contain a plate-like inorganic compound, a coupling agent, cyclodextrin and / or a derivative thereof, and the like.
[0105] As the polyester polyol having two or more hydroxyl groups in one molecule as a functional group, for example, the following [First Example] to [Third Example] can be used. [Example 1] Polyester polyol obtained by polycondensation of ortho-oriented polycarboxylic acid or its anhydride with polyhydric alcohol [Example 2] Polyester polyol with glycerol structure [Example 3] Polyester polyol with isocyanuric ring Each polyester polyol will be described below.
[0106] The polyester polyol according to the first example is a polycondensate obtained by polycondensing a polycarboxylic acid component containing at least one or more types of orthophthalic acid and its anhydride, and a polyhydric alcohol component containing at least one type selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol. In particular, polyester polyols in which the content of orthophthalic acid or its anhydride in the total polyvalent carboxylic acid components is 70 to 100 mass % are preferred.
[0107] The polyester polyol according to the first example essentially contains orthophthalic acid and its anhydride as the polycarboxylic acid component, but may be copolymerized with other polycarboxylic acid components as long as the effect of the present embodiment is not impaired. Specifically, the polybasic acids include aliphatic polybasic carboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecane dicarboxylic acid, unsaturated bond-containing polybasic carboxylic acids such as maleic anhydride, maleic acid, and fumaric acid, alicyclic polybasic carboxylic acids such as 1,3-cyclopentane dicarboxylic acid and 1,4-cyclohexane dicarboxylic acid, aromatic polybasic carboxylic acids such as terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyl dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, anhydrides of these dicarboxylic acids, and ester-forming derivatives of these dicarboxylic acids, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids. Among these, succinic acid, 1,3-cyclopentane dicarboxylic acid, and isophthalic acid are preferred. Two or more of the above other polyvalent carboxylic acids may be used.
[0108] As a polyester polyol according to a second example, a polyester polyol having a glycerol skeleton represented by general formula (1) can be mentioned. [ka] In general formula (1), R1, R2, and R3 each independently represent H (hydrogen atom) or a group represented by the following general formula (2). [ka]
[0109] In formula (2), n represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of 1,2-phenylene groups, 1,2-naphthylene groups, 2,3-naphthylene groups, 2,3-anthraquinonediyl groups, and 2,3-anthracenediyl groups, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 represents a group represented by general formula (2).
[0110] In general formula (1), at least one of R1, R2, and R3 must be a group represented by general formula (2). In particular, it is preferable that all of R1, R2, and R3 are groups represented by general formula (2).
[0111] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (2), a compound in which any two of R1, R2, and R3 are groups represented by general formula (2), and a compound in which all of R1, R2, and R3 are groups represented by general formula (2).
[0112] X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group. When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0113] In the general formula (2), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0114] The polyester resin compound having a glycerol skeleton represented by general formula (1) can be synthesized by reacting glycerol, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0115] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride. These compounds may have a substituent at any carbon atom of the aromatic ring, such as a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.
[0116] Examples of the polyhydric alcohol component include alkylene diols having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, and dimethylbutanediol.
[0117] The polyester polyol according to the third example is a polyester polyol having an isocyanuric ring represented by the following general formula (3). [ka] In the general formula (3), R1, R2, and R3 each independently represent "-(CH2)n1-OH (wherein n1 represents an integer of 2 to 4)" or a structure represented by the general formula (4). [ka]
[0118] In the general formula (4), n2 represents an integer of 2 to 4, n3 represents an integer of 1 to 5, X represents an arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group, which may have a substituent, and Y represents an alkylene group having 2 to 6 carbon atoms. However, at least one of R1, R2, and R3 is a group represented by the general formula (4).
[0119] In the general formula (3), the alkylene group represented by -(CH2)n1- may be linear or branched. Among them, n1 is preferably 2 or 3, and most preferably 2.
[0120] In the general formula (4), n2 represents an integer of 2 to 4; n3 represents an integer of 1 to 5. X represents an optionally substituted arylene group selected from the group consisting of a 1,2-phenylene group, a 1,2-naphthylene group, a 2,3-naphthylene group, a 2,3-anthraquinonediyl group, and a 2,3-anthracenediyl group.
[0121] When X is substituted, it may be substituted with one or more substituents, and the substituent is attached to any carbon atom on X other than the free radical. The substituents include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, a N-ethylcarbamoyl group, a phenyl group, and a naphthyl group. The substituent for X is preferably a hydroxyl group, a cyano group, a nitro group, an amino group, a phthalimido group, a carbamoyl group, an N-ethylcarbamoyl group, or a phenyl group, and most preferably a hydroxyl group, a phenoxy group, a cyano group, a nitro group, a phthalimido group, or a phenyl group.
[0122] In the general formula (4), Y represents an alkylene group having 2 to 6 carbon atoms, such as an ethylene group, a propylene group, a butylene group, a neopentylene group, a 1,5-pentylene group, a 3-methyl-1,5-pentylene group, a 1,6-hexylene group, a methylpentylene group, or a dimethylbutylene group. Among these, Y is preferably a propylene group or an ethylene group, and most preferably an ethylene group.
[0123] In general formula (3), at least one of R1, R2, and R3 is a group represented by general formula (4). Of these, it is preferable that all of R1, R2, and R3 are groups represented by general formula (4).
[0124] In addition, the compound may be a mixture of two or more of a compound in which any one of R1, R2, and R3 is a group represented by general formula (4), a compound in which any two of R1, R2, and R3 are groups represented by general formula (4), and a compound in which all of R1, R2, and R3 are groups represented by general formula (4).
[0125] The polyester polyol having an isocyanuric ring represented by the general formula (3) can be synthesized by reacting a triol having an isocyanuric ring, an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and a polyhydric alcohol component as essential components.
[0126] Examples of triols having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid.
[0127] Examples of aromatic polycarboxylic acids or anhydrides in which a carboxylic acid is substituted at the ortho position include orthophthalic acid or anhydride, naphthalene 2,3-dicarboxylic acid or anhydride, naphthalene 1,2-dicarboxylic acid or anhydride, anthraquinone 2,3-dicarboxylic acid or anhydride, and 2,3-anthracene carboxylic acid or anhydride, etc. These compounds may have a substituent on any carbon atom of the aromatic ring.
[0128] Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimido group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, and a naphthyl group.
[0129] The polyhydric alcohol component may be an alkylene diol having 2 to 6 carbon atoms, such as ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, or dimethylbutanediol. Among these, polyester polyol compounds having an isocyanuric ring, which use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid as a triol compound having an isocyanuric ring, orthophthalic anhydride as an aromatic polycarboxylic acid or its anhydride in which a carboxylic acid is substituted at the ortho position, and ethylene glycol as a polyhydric alcohol, are particularly excellent in oxygen barrier properties and adhesion and are therefore preferred.
[0130] The isocyanuric ring is highly polar and trifunctional, and can increase the polarity of the entire system and increase the crosslink density. From this viewpoint, it is preferable that the adhesive resin contains 5% by mass or more of the isocyanuric ring based on the total solid content of the adhesive resin.
[0131] The isocyanate compound has two or more isocyanate groups in the molecule. The isocyanate compound may be either aromatic or aliphatic, and may be either a low molecular weight compound or a high molecular weight compound. Furthermore, the isocyanate compound may be a blocked isocyanate compound obtained by subjecting a known isocyanate blocking agent to an addition reaction by a known, conventional appropriate method. Among these, from the viewpoints of adhesiveness and retort resistance, polyisocyanate compounds having three or more isocyanate groups are preferred, and from the viewpoints of oxygen barrier property and water vapor barrier property, aromatic compounds are preferred.
[0132] Specific examples of the isocyanate compound include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, metaxylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and trimers of these isocyanate compounds, as well as adducts, biurets, and allophanates obtained by reacting these isocyanate compounds with low-molecular-weight active hydrogen compounds or their alkylene oxide adducts, or high-molecular-weight active hydrogen compounds. Examples of low molecular weight active hydrogen compounds include ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine. Examples of molecular weight active hydrogen compounds include polymeric active hydrogen compounds such as various polyester resins, polyether polyols, and polyamides.
[0133] The phosphoric acid-modified compound is, for example, a compound represented by the following general formula (5) or (6). [ka] In general formula (5), R1, R2, and R3 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms which has a (meth)acryloyloxy group, at least one of which is a hydrogen atom, and n is an integer of 1 to 4. [ka] In the formula, R4 and R5 are groups selected from a hydrogen atom, an alkyl group having 1 to 30 carbon atoms, a (meth)acryloyl group, a phenyl group which may have a substituent, and an alkyl group having 1 to 4 carbon atoms and having a (meth)acryloyloxy group, n is an integer of 1 to 4, x is an integer of 0 to 30, and y is an integer of 0 to 30, except for the case where both x and y are 0.
[0134] More specific examples include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl) phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, and polyoxyethylene alkyl ether phosphate, and one or more of these can be used.
[0135] The content of the phosphoric acid-modified compound in the resin composition is preferably from 0.005% by mass to 10% by mass, and more preferably from 0.01% by mass to 1% by mass. By making the content of the phosphoric acid-modified compound 0.005% by mass or more, the oxygen barrier property and water vapor barrier property of the laminate of the present invention can be improved, and by making the content of the phosphoric acid-modified compound 10% by mass or less, the adhesiveness of the adhesive layer can be improved.
[0136] The resin composition containing the polyester polyol, the isocyanate compound and the phosphoric acid-modified compound may contain a plate-like inorganic compound, which can improve the adhesiveness of the adhesive layer and the bending load resistance of the laminate of the present invention. Examples of the plate-like inorganic compounds include kaolinite-serpentine group clay minerals (such as halloysite, kaolinite, endelite, dickite, nacrite, antigorite, and chrysotile) and pyrophyllite-talc group (such as pyrophyllite, talc, and keroli).
[0137] Examples of the coupling agent include silane-based coupling agents, titanium-based coupling agents, and aluminum-based coupling agents represented by the following general formula (7). These coupling agents may be used alone or in combination of two or more kinds. [ka]
[0138] Examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-methacryloxytrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldiethoxysilane, γ-methacryloxypropyltriethoxysilane, N-β( aminoethyl) γ-aminopropyl methyl dimethoxysilane, N-β (aminoethyl) γ-aminopropyl trimethoxysilane, N-β (aminoethyl) γ-aminopropyl triethoxysilane, γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, γ-chloropropyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-acryloxypropyl trimethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylidene).
[0139] Examples of titanium-based coupling agents include isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, tetraoctyl bis(didodecyl phosphite) titanate, tetraoctyl bis(ditridecyl phosphite) titanate, bis(dioctyl pyrophosphate)oxyacetate titanate, bis(dioctyl pyrophosphate)ethylene titanate, isopropyl trioctyl nor titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl isostearoyl diacryl titanate, diisostearoyl ethylene titanate, isopropyl tri(dioctyl phosphate) titanate, isopropyl tricumyl phenyl titanate, and dicumyl phenyl oxyacetate titanate.
[0140] Specific examples of aluminum-based coupling agents include acetoalkoxyaluminum diisopropylate, diisopropoxyaluminum ethyl acetoacetate, diisopropoxyaluminum monomethacrylate, isopropoxyaluminum alkyl acetoacetate mono(dioctyl phosphate), aluminum 2-ethylhexanoate oxide trimer, aluminum stearate oxide trimer, and alkyl acetoacetate aluminum oxide trimer.
[0141] The resin composition may contain cyclodextrin and / or a derivative thereof, which can improve the adhesiveness of the adhesive layer and can further improve the bending load resistance of the laminate of the present invention. Specifically, for example, cyclodextrin, alkylated cyclodextrin, acetylated cyclodextrin, hydroxyalkylated cyclodextrin, and other cyclodextrins in which the hydrogen atom of the hydroxyl group of the glucose unit of cyclodextrin is substituted with another functional group can be used. Branched cyclic dextrins can also be used. Furthermore, the cyclodextrin skeleton in cyclodextrin and cyclodextrin derivatives may be any of α-cyclodextrin consisting of six glucose units, β-cyclodextrin consisting of seven glucose units, and γ-cyclodextrin consisting of eight glucose units. These compounds may be used alone or in combination of two or more. Hereinafter, these cyclodextrins and / or their derivatives may be collectively referred to as dextrin compounds.
[0142] From the viewpoint of compatibility and dispersibility in the resin composition, it is preferable to use a cyclodextrin derivative as the cyclodextrin compound.
[0143] Examples of alkylated cyclodextrins include methyl-α-cyclodextrin, methyl-β-cyclodextrin, and methyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.
[0144] Examples of acetylated cyclodextrin include monoacetyl-α-cyclodextrin, monoacetyl-β-cyclodextrin, and monoacetyl-γ-cyclodextrin. These compounds may be used alone or in combination of two or more.
[0145] Examples of hydroxyalkylated cyclodextrins include hydroxypropyl-α-cyclodextrin, hydroxypropyl-β-cyclodextrin, and hydroxypropyl-γ-cyclodextrin, etc. These compounds may be used alone or in combination of two or more kinds.
[0146] The thickness of the adhesive layer is preferably 0.5 μm or more and 6 μm or less, more preferably 0.8 μm or more and 5 μm or less, and even more preferably 1 μm or more and 4.5 μm or less. By making the thickness of the adhesive layer 0.5 μm or more, the adhesiveness of the adhesive layer can be improved. In addition, when the adhesive layer is made of a cured product of a resin composition containing a polyester polyol, an isocyanate compound, and a phosphoric acid-modified compound, the bending load resistance of the laminate can be improved. By setting the thickness of the adhesive layer to 6 μm or less, the processability of the laminate can be improved.
[0147] The adhesive layer can be formed by applying the adhesive onto a substrate or the like and drying it using a conventional method such as a direct gravure roll coating method, a gravure roll coating method, a kiss coating method, a reverse roll coating method, a Fontaine method, or a transfer roll coating method.
[0148] The laminate of the present invention can be particularly suitably used for the packaging material applications described below.
[0149] (packaging material) The packaging material of the present invention is characterized in that it is composed of the above-mentioned laminate. The shape of the packaging material is not particularly limited, and may be in the form of a bag as shown in FIG. In the figure, the shaded areas indicate the heat-sealed areas.
[0150] In one embodiment, a bag-shaped packaging material can be produced by folding the laminate of the present invention in half, overlapping the laminate so that the heat seal layer is on the inside, and heat sealing the ends. In another embodiment, the bag-shaped packaging material can also be produced by overlapping two laminates with their heat-sealable layers facing each other, and heat-sealing the ends thereof.
[0151] The heat sealing method is not particularly limited, and can be performed by a known method such as bar sealing, rotary roll sealing, belt sealing, impulse sealing, high frequency sealing, ultrasonic sealing, etc.
[0152] In one embodiment, the packaging material has a shape of a stand-up pouch having a body and a bottom, as shown in FIG.
[0153] A packaging material in the form of a stand-up pouch can be produced by heat-sealing the above-mentioned laminate into a cylindrical shape with the heat-seal layer on the inside to form a body, and then folding another laminate into a V shape with the heat-seal layer on the inside, sandwiching it from one end of the body, and heat-sealing it to form a bottom.
[0154] The contents filled in the packaging material are not particularly limited, and may be liquid, powder, or gel. In addition, the contents may be food or non-food. After filling the container with the contents, the opening can be heat sealed to form a package. EXAMPLES
[0155] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0156] Example 1 Biomass-derived linear low-density polyethylene (density: 0.916 g / cm 3 A polyethylene film having a thickness of 100 μm was produced by extrusion molding using a polyethylene terephthalate (SLL18, product name: SLL18, MFR: 1.3 g / 10 min, biomass ratio: 87%, manufactured by Braskem). This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a film with a thickness of 20 μm.
[0157] Next, one surface of the film was irradiated with electron beams using an electron beam irradiation device (line irradiation type irradiation device EZ-CURE, manufactured by Iwasaki Electric Co., Ltd.) under the following conditions to obtain a substrate. Voltage: 100kV Irradiation dose: 280kGy Oxygen concentration inside the device: 100ppm or less Line speed: 25m / min
[0158] An image was formed on the surface of the substrate opposite to the surface irradiated with the electron beam by gravure printing using oil-based gravure ink (manufactured by DIC Graphics, Inc., trade name: Finart).
[0159] A 40 μm-thick unstretched linear low-density polyethylene film (manufactured by Mitsui Chemicals Tocello Co., Ltd., product name: TUX-TCS) was prepared as a heat seal layer, and laminated to the image forming surface of the substrate via the above-mentioned two-component curing urethane-based adhesive (manufactured by Rock Paint Co., Ltd., product name: RU-77T / H-7) to obtain a laminate of the present invention. The adhesive layer formed from the two-component curing urethane adhesive had a thickness of 3.0 μm.
[0160] Example 2 A laminate was produced in the same manner as in Example 1, except that an aluminum vapor deposition film having a thickness of 20 nm was formed by PVD on the substrate lamination surface of the LLDPE film.
[0161] Example 3 Medium density polyethylene (density: 0.941 g / cm3, melting point: 129°C, MFR: 1.3 g / 10 min, Dow Chemical, product name: Elite5538G) was formed into a film by inflation molding to obtain a polyethylene film having a thickness of 100 µm. This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a film with a thickness of 20 μm.
[0162] An aluminum film having a thickness of 20 nm was formed by vapor deposition on one surface of the polyethylene film thus obtained by the PVD method to prepare an intermediate layer.
[0163] The above adhesive was applied to the surface of the intermediate layer on which the vapor-deposited film was formed, and the image-forming surface of the substrate prepared in Example 1 was laminated thereon.
[0164] The above adhesive was applied to the surface of the intermediate layer on which the vapor-deposited film was not formed, and the above LLDPE film having a thickness of 40 μm was laminated thereon to obtain a laminate of the present invention.
[0165] Example 4 The heat seal layer was made of linear low-density polyethylene (density: 0.925, MFR: 1.9 g / 10 min, Prime Polymer, product name: SP2520) and biomass-derived linear low-density polyethylene (density: 0.916 g / cm 3 A laminate of the present invention was obtained in the same manner as in Example 1, except that a polyethylene film having a linear low-density polyethylene layer (10 μm), a biomass-derived linear low-density polyethylene layer (20 μm), and a linear low-density polyethylene layer (10 μm) in this order was formed from a polyethylene terephthalate (PE)-based polymer (MFR: 1.3 g / 10 min, biomass degree: 87%, manufactured by Braskem, product name: SLL18) was formed by an inflation molding method.
[0166] Comparative Example 1 The above-mentioned biomass-derived linear low-density polyethylene was formed into a film by inflation molding to obtain a polyethylene film having a thickness of 20 μm. A laminate was produced in the same manner as in Example 1, except that the substrate was changed to the polyethylene film.
[0167] Comparative Example 2 A laminate was produced in the same manner as in Comparative Example 1, except that one surface of the polyethylene film produced in Comparative Example 1 was irradiated with an electron beam in the same manner as in Example 1.
[0168] Comparative Example 3 The above-mentioned biomass-derived linear low-density polyethylene was formed into a film by inflation molding to obtain a polyethylene film having a thickness of 100 μm. This polyethylene film was stretched in the machine direction (MD) at a stretching ratio of 5 times to obtain a polyethylene film having a thickness of 20 μm. A laminate was produced in the same manner as in Example 1, except that the substrate was changed to the polyethylene film.
[0169] Comparative Example 4 A laminate was obtained in the same manner as in Example 1, except that the substrate was a biaxially stretched polyester film having a thickness of 12 μm (manufactured by Toyobo Co., Ltd., product name: E5100).
[0170] <<Recyclability evaluation>> The recyclability of the laminates obtained in the above Examples and Comparative Examples was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ◯: The polyethylene content in the laminate was 90% by mass or more. ×: The polyethylene content in the laminate was less than 90% by mass.
[0171] <<Strength evaluation>> The laminates produced in the above examples and comparative examples were measured for strength when pierced with a needle having a diameter of 0.5 mm using a tensile tester (manufactured by Orientec Co., Ltd., product name: RTC-1310A). The piercing speed was set to 50 mm / min. The measurement results are summarized in Table 1.
[0172] <<Heat resistance evaluation>> Two test pieces each measuring 80 mm long x 80 mm wide were prepared from the laminates obtained in the above-mentioned Examples and Comparative Examples. Two test pieces were overlapped with the heat seal layers facing each other, and three sides were heat sealed at 150°C to prepare a small pouch-shaped packaging material. The produced packaging material was visually observed, and the heat resistance of the laminate was evaluated based on the following evaluation criteria. The evaluation results are summarized in Table 1. (Evaluation Criteria) ⊚: No wrinkles or the like were observed on the surface of the packaging material, and no adhesion to the heat seal bar was observed. ◯: A few wrinkles were observed on the surface of the packaging material, and a small amount of adhesion to the heat seal bar was observed, but this was not problematic for practical use. ×: Wrinkles or the like were generated on the surface of the packaging material, and adhesion to the heat seal bar was observed, and bags could not be made.
[0173] <<Oxygen Barrier Evaluation>> The laminates obtained in the above Examples and Comparative Examples were cut to A4 size, and the oxygen permeability (cc / m) was measured using OXTRAN 2 / 20 manufactured by MOCON, USA, at 23°C and a relative humidity of 90%. 2 / day / atm) were measured. The measurement results are summarized in Table 1. The upper limit of measurement is 200cc / m 2 For amounts exceeding / day / atm, "-" is displayed.
[0174] <<Water vapor barrier property evaluation>> The laminates obtained in the above Examples and Comparative Examples were cut to A4 size, and the water vapor permeability (g / m) was measured under an environment of 40°C and a relative humidity of 90% using a PERMATRAN 3 / 31 manufactured by MOCON, USA. 2 / day / atm) were measured. The measurement results are summarized in Table 1.
[0175] <<Heat sealability test>> The laminates obtained in the above Examples and Comparative Examples were cut to a size of 10 cm x 10 cm to prepare sample pieces. The sample pieces were folded in half so that the heat seal layer was on the inside, and then heated at a temperature of 140°C and a pressure of 1 kgf / cm. 2 An area of 1 cm x 10 cm was heat sealed under the conditions of 100° C., 1 sec. The heat-sealed sample pieces were cut into strips with a width of 15 mm, and both ends that were not heat-sealed were held in a tensile tester to measure the peel strength (N / 15 mm) at a speed of 300 mm / min and a load range of 50 N. The measurement results are summarized in Table 1. The laminate obtained in Comparative Example 1 was marked "-" since the peel strength could not be measured because the laminate adhered to the heat seal bar.
[0176] [Table 1] [Explanation of symbols]
[0177] 10: laminate, 11: substrate, 12: heat seal layer, 13: intermediate layer, 14: adhesive layer
Claims
1. A laminate comprising a substrate and a heat seal layer, The substrate and the heat seal layer are made of polyethylene, At least one surface of the substrate is irradiated with an electron beam; The substrate is subjected to a stretching treatment, At least one of the substrate and the heat seal layer contains biomass-derived polyethylene as the polyethylene, The content of polyethylene in the entire laminate is 90% by mass or more, A laminate, characterized in that the substrate is provided so that the surface of the substrate that is irradiated with an electron beam is the outermost surface.
2. The laminate according to claim 1 , wherein the substrate has a thickness of 10 μm or more and 50 μm or less.
3. The laminate according to claim 1 or 2, wherein the stretching ratio of the substrate in the longitudinal direction and / or the transverse direction is 2 times or more and 10 times or less.
4. The laminate according to any one of claims 1 to 3, which is used for packaging material applications.
5. A packaging material comprising the laminate according to any one of claims 1 to 4.
6. A packaging bag, The laminate according to any one of claims 1 to 4 is used. A packaging bag, characterized in that the heat seal layer has a thickness of 20 μm or more and 60 μm or less.
7. It is a stand-up pouch, The laminate according to any one of claims 1 to 4 is used. A stand pouch, characterized in that the heat seal layer has a thickness of 50 μm or more and 200 μm or less.